Evaluation of fluorescent Pseudomonads and Trichoderma for growth promotion and control of soil borne diseases of groundnut: Evaluation of fluorescent Pseudomonads and Trichoderma for growth promotion and control of soil borne diseases of groundnut - P REVATH; M VENKATAIAH; P GONYA NAIK (Journal of Oilseeds Research, 2020)
A potential method for suppressing soil-borne pathogens is to apply, or encourage growth of, plant growth– promoting rhizobacteria. Many isolates of P. fluorescens are efficacious for improving plant growth and yields and for suppressing soil-borne plant pathogens. The antibiotic DAPG (2,4-diacetylphloroglucinol) is one of the metabolites produced by Pseudomonas which can suppress other pathogens, and can affect plant vigor, including root weights and lengths and root branching and trigger induced systemic resistance (ISR). In the present investigation, three DAPGproducing and 2 non- DAPG producing fluorescent pseudomonads and a Trichoderma strain were found effective in amelioration of biotic and abiotic stresses and enhance groundnut seed yield.